AN OVER REVIEW ON EFFECT OF AFLATOXIN IN ANIMAL HUSBANDRY - E. TALEBI,; M. KHADEMI,; A. RASTAD, (The Bioscan, 2011)
Aflatoxins are toxic metabolites produced by a variety of molds such as Aspergillus flavus and Aspergillus parasiticus. They are carcinogenic and can be present in grains, nuts, cottonseeds and other commodities associated with human food or animal feeds. Aflatoxins have been implicated in human health disorders including hepatocellular carcinoma, aflatoxicosis, Rey’s syndrome and chronic hepatitis. Symptoms of toxicity in animals range from death to chronic diseases, reproductive interference, immune suppression, decreased milk and egg production.